Demystifying modern slavery - Broad, Rosemary; Gadd, David, 1975- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Who are the perpetrators of modern slavery? Why do they exploit others and what might be done to stop exploitation recurring? These are the questions answered in this book. Reporting on the first primary study of modern slavery offenders, the book depicts the findings of in-depth interviews with people accused of, and convicted for, committing modern slavery offences. The different forms modern slavery takes are explained chapter by chapter: organised crime, people smuggling, labour exploitation, domestic servitude, sham marriage, the trafficking of adults for sexual exploitation and child sex trafficking. Using case studies to illuminate the perspectives of those deemed perpetrators, we show that few modern slavery offenders conform to stereotypes of people traffickers. Through an interpretive analysis of offenders' life-stories, we reveal the points in the past and present where interventions could have prevented victims from becoming trapped in exploitation. We show that while national governments and international bodies often appear resolute in their efforts to tackle modern slavery and people trafficking, they have also obscured their own roles in compounding the plights of those at the sharp ends of globalization. In racializing the actions of sex traffickers, grooming gangs, and organised criminals, the modern slavery agenda has mystified the roles market dynamics, the absence of workers' rights, and immigration controls play in generating vulnerabilities to exploitation. This book will be of interest to a wide range of students, policymakers and practitioners concerned with modern slavery, human trafficking, border control and immigration, globalization and inequality, as well as the more discipline-focused criminological audiences concerned with why people commit crimes, what should be done about them and the, often paradoxical, consequences of social control across borders. Given the book's strong focus on narrative, psychosocial and social network methodologies it will also appeal to audiences across the social sciences concerned with applying these novel approaches to difficult to reach populations"--
Introduction -- Demystifying Modern Slavery -- Evil Slave Masters as Political Folk Devils -- People Smuggling -- Organised Criminals? -- Sham Marriage -- Domestic Servitude -- Labour Exploitation -- Adult Sex Trafficking -- Child Sexual Exploitation -- Conclusion.
Keywords: Slavery -- History -- 21st century; Human trafficking -- History -- 21st century; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Emigration & Immigration